Global economy and the euro area: Protectionism weighing on trade and investment - Claus Michelsen; Guido Baldi; Geraldine Dany-Knedlik; Hella Engerer; Stefan Gebauer; Malte Rieth (DIW Weekly Report, 2019)
The global economy is holding steady amidst uncertainty, although subdued export and investment growth in some places is already proving the extent to which protectionism and the unresolved trade conflicts are negatively affecting the economy. Contributing to the uncertainty is the continued unclear outcome of Brexit. In many countries, the domestic economy is fighting against a downturn. However, the situation on the labor market remains good overall and employment and wages are rising, leading many private households to spend some of the extra money. Although DIW Berlin expects the global economy to slow in 2019 and 2020, with growth of 3.7 percent for each year, its forecast remains largely stable compared to the spring of this year.
Keywords: E32; E66; F01; 330; business cycle forecast; ecoomic outlook